The Downsides of Extreme Conscientiousness for Psychological Well‐being: The Role of Obsessive Compulsive Tendencies. Issue 4 (6th May 2015) - Carter, Nathan T.; Guan, Li; Maples, Jessica L.; Williamson, Rachel L.; Miller, Joshua D.
Abstract: Although conscientiousness exhibits positive relations with psychological well‐being, theoretical and empirical work suggests individuals can be too conscientious, resulting in obsessive‐compulsiveness, and therein less positive individual outcomes. However, the potential for curvilinearity between conscientiousness and well‐being has been underexplored. We measured 912 subjects on facets of conscientiousness, obsessive‐compulsive personality, and well‐being variables (life satisfaction, job satisfaction, self‐esteem, positive affect, negative affect, work stress). Methods of scoring included traditional sum‐scoring, traditional item response theory (IRT), and a relatively new IRT approach. Structural models were estimated to evaluate curvilinearity. Results confirmed the curvilinear relationship between conscientiousness and well‐being, and demonstrated that differential facet‐level relationships underlie weaker curvilinearity at the general trait level. Consistency was found in the strength of relation between conscientiousness facets with their obsessive‐compulsive variants and their contribution to decreased well‐being. The most common association was that higher standing on conscientiousness facets was positively related to negative affect. Findings support the idea that extreme standing on facets of conscientiousness more strongly linked to their obsessive‐compulsive variants contributed to lower well‐being, highlighting the importance of considering alternative functional representations of the relationship between personality and other constructs. Future work should seek to further clarify the link between conscientiousness and negative affect.